Positive electrode catalyst for lithium-air battery, positive electrode and lithium-air battery

By using heterostructured materials as the positive electrode catalyst in lithium-air batteries, combining zero-valent metals and metal oxides to form a core-shell structure, the problems of poor conductivity and poor discharge products of lithium-air batteries are solved, and the specific capacity and cycling stability are significantly improved.

CN119725579APending Publication Date: 2025-03-28ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510122925.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Lithium-air batteries have problems with high overpotential and poor cycle stability, mainly due to poor conductivity of metal oxides and poor morphology of discharge products.

Method used

Heterostructured materials are used as the positive electrode catalyst, including a combination of zero-valent metal and metal oxides, to form a core-shell structure, such as Fe@FeOx, Co@Co3O4, Cu@CuO, etc., and are prepared by thermal oxidation method, electrochemical oxidation method and other methods.

Benefits of technology

It significantly improves the comprehensive performance of lithium-air batteries, improves specific capacity and cycle stability, and solves the problems of poor conductivity and poor morphology of discharge products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259289720000061
    Figure BDA0005259289720000061
  • Figure BDA0005259289720000071
    Figure BDA0005259289720000071
  • Figure HDA0005259289730000011
    Figure HDA0005259289730000011
Patent Text Reader

Abstract

The invention discloses a positive electrode catalyst for a lithium-air battery, a positive electrode and the lithium-air battery. The positive electrode catalyst material is a heterostructure material, the heterostructure material is composed of one or more zero-valent metals and at least one metal oxide, and the metals are at least one of Pd, Pt, Sn, Ti, V, Mn, Fe, Co, Ni, Cu and Zn. The positive electrode comprises the positive electrode catalyst material. The lithium-air battery comprises the positive electrode. The positive electrode catalyst material provided by the invention can significantly improve the comprehensive performance of the battery, and shows excellent specific capacity and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-air batteries, and in particular to a positive electrode catalyst for lithium-air batteries, a positive electrode and a lithium-air battery. Background Art

[0002] Lithium-air batteries have attracted extensive attention from researchers due to their extremely high theoretical specific capacity. However, due to the insolubility and insulation of their discharge products and the slow ORR / OER kinetics, they have disadvantages such as high overpotential and poor cycle stability. Developing efficient cathode catalysts is one of the best ways to solve the above problems. The mainstream catalysts reported so far include carbon materials, precious metals and their oxides, and non-precious metals and their oxides. Carbon materials are basically not used alone as cathode catalysts because they catalyze the decomposition of electrolytes and have limited catalytic performance.

[0003] The transmission and transfer rate of electrons between catalysts and reactants is a key factor in evaluating their catalytic effect. Metals have better electron conductivity than their oxides, carbides and sulfides. Zero-valent metals such as Pt and Pd are widely reported as positive electrode catalysts in lithium-air batteries, but they are easily oxidized and deactivated under high-pressure oxygen-rich conditions; TiO2, V2O5, Mn2O3, MnO2, Fe2O3 and other oxides widely studied in lithium-air batteries have the disadvantage of poor conductivity. Many researchers have improved their conductivity and catalytic effect by introducing oxygen vacancies. Achieving a catalytic system with both high conductivity and high catalytic activity is an urgent problem to be solved in the field of lithium-air batteries. Summary of the invention

[0004] In order to optimize the morphology of discharge products and solve the problems of short cycle life and low specific capacity of lithium-air batteries caused by poor conductivity of metal oxides, the present invention provides a positive electrode catalyst, a positive electrode and a lithium-air battery for lithium-air batteries. The provided positive electrode catalyst material can significantly improve the comprehensive performance of the battery, showing excellent specific capacity and cycle stability.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a positive electrode catalyst material for a lithium-air battery, wherein the positive electrode catalyst material is a heterogeneous structure material, wherein the heterogeneous structure material is composed of one or more zero-valent metals and at least one metal oxide, and the metal is at least one of Pd, Pt, Sn, Ti, V, Mn, Fe, Co, Ni, Cu, and Zn.

[0007] Preferably, the heterostructure material is a core-shell structure, with a zero-valent metal as the core and a metal oxide layer as the shell, such as Fe@FeOx Micro-nanoparticles, Co@Co3O4 nanoparticles, Cu@CuO nanosheets, Sn@SnO x Micro-nanoparticles, Zn@ZnO x Micro-nano size materials, among which FeO x SnO x 、ZnO x All refer to the corresponding oxides of Fe, Sn and Zn.

[0008] As a further preference, in the heterostructure material, the thickness of the metal oxide layer does not exceed 20 nm.

[0009] The cathode catalyst material of the present invention may be in the form of particles, rods, two-dimensional sheets, etc., preferably in the form of micrometers and / or nanometers, especially nanometers.

[0010] The heterogeneous structure material described in the present invention can be prepared by existing methods according to the structural design, such as thermal oxidation method, electrochemical oxidation method, hydrothermal method, etc.

[0011] As an embodiment, the heterostructure material Fe@FeO x The micro-nano particles were prepared by thermal oxidation. The specific steps are as follows: Fe metal particles with a particle size of 10-1000 nm were used as catalyst precursors, which were placed in a muffle furnace and calcined at 300℃-500℃ for 0.5-2h to form a mixed valence oxide layer on the surface of the Fe metal particles to obtain the heterogeneous structure material Fe@FeO x .

[0012] As an embodiment, the heterostructure material Co@Co3O4 nanoparticles are prepared by the following steps:

[0013] Step 1: Synthesis of Co3O4@MgO nanoparticles by sol-gel method:

[0014] Dissolve Mg(NO3)2·6H2O and citric acid in water, add Co3O4 nanoparticles and fully disperse them, wherein the Mg(NO3)2·6H2O and Co3O4 nanoparticles are fed in a stoichiometric mass ratio of Co3O4 to MgO of 1:1-1:3; stir the resulting suspension at 70-90°C until a gel is formed; dry the resulting gel and anneal at 600-1000°C for 3-6h to crystallize MgO to obtain Co3O4@MgO nanoparticles;

[0015] Step 2: reducing the Co3O4@MgO nanoparticles at high temperature in a H2 / N2 mixed atmosphere (hydrogen volume content is 5-10%) to obtain Co@MgO nanoparticles; preferably, the reduction temperature is 800-1000°C and the reduction time is 4-8h;

[0016] Step 3: annealing the Co@MgO nanoparticles at 500-900° C. (preferably 700° C.) in air to obtain Co@Co3O4@MgO nanoparticles;

[0017] Step 4: Wash the Co@Co3O4@MgO nanoparticles with acid (preferably hydrochloric acid) to remove MgO, and wash (preferably with anhydrous ethanol) to obtain Co@Co3O4 nanoparticles.

[0018] As an embodiment, the heterostructure material Cu@CuO is prepared by the following steps:

[0019] Step 1: Obtaining Cu nanoparticles;

[0020] Step 2: Mix Cu nanoparticles, deionized water and NaOH in a reactor and stir. Subsequently, drip H2O2 into the reactor, then close the reactor, heat to 90-110°C, maintain for 8-14 hours, cool, and rinse with deionized water and ethanol respectively. The final product is CuO@Cu nanosheets; the molar ratio of Cu nanoparticles, NaOH and H2O2 is 10:1-3:1-4.

[0021] The heterostructure material of the present invention can also be formed in situ during the charge and discharge process of the lithium-air battery. As an embodiment, when the metal element is selected from at least one of Sn, Fe, Co, Ni, Cu, and Zn, the metal element is directly used as a catalyst precursor to prepare the positive electrode. During the charge and discharge process of the lithium-air battery, the catalyst precursor can be activated into a heterostructure, that is, a layer of metal oxide is coated on the surface of the metal element. Preferably, the catalyst precursor can be granular, rod-shaped, two-dimensional sheet, etc., preferably micrometer and / or nanometer size, especially nanometer size.

[0022] In a second aspect, the present invention provides a positive electrode for a lithium-air battery, comprising the positive electrode catalyst material described in the first aspect.

[0023] As an embodiment, the positive electrode for the lithium-air battery includes carbon paper and a positive electrode catalyst material and a binder coated on the carbon paper. Preferably, the binder is polyvinylidene fluoride or polytetrafluoroethylene. Preferably, the mass ratio of the positive electrode catalyst material and the binder is 70-90%:10-30%. The positive electrode can be prepared by the following method: dripping the slurry containing the positive electrode catalyst material and the binder described in the first aspect on the carbon paper, and obtaining the positive electrode after drying; when the metal in the positive electrode catalyst material is selected from at least one of Sn, Fe, Co, Ni, Cu, and Zn, the positive electrode catalyst material is added in the form of a heterogeneous structure material or a metal element (i.e., a catalyst precursor), and the added metal element is activated into a heterogeneous structure during the charge and discharge process of the lithium-air battery. Preferably, the dispersant of the slurry is NMP or DMF. Preferably, the slurry also contains a conductive agent, and the conductive agent is conductive carbon black, Super P or CNT. It is further preferred that the mass ratio of the positive electrode catalyst material to the binder and the conductive agent in the slurry is 50-80%:10-30%:10-20%. Preferably, the drying condition is: vacuum drying at 80°C to 100°C for 10h to 12h.

[0024] As an embodiment, the positive electrode for the lithium-air battery is a self-supporting electrode, and the self-supporting electrode includes a porous metal current collector and a metal element deposited on the current collector, and the metal element is selected from at least one of Sn, Fe, Co, Ni, Cu, and Zn. The metal element is activated into a heterogeneous structure during the charge and discharge process of the lithium-air battery. The self-supporting electrode is specifically prepared by the following method: a metal element (such as Zn) is deposited on a porous metal current collector (such as a nickel foam sheet) by electrodeposition.

[0025] In a third aspect, the present invention provides a lithium-air battery, wherein the lithium-air battery comprises the positive electrode described in the second aspect.

[0026] The lithium-air battery of the present invention further comprises:

[0027] A negative electrode, wherein the negative electrode is a lithium sheet;

[0028] electrolyte; and

[0029] A separator is located between the positive electrode and the negative electrode.

[0030] The electrolyte of the present invention may be an electrolyte conventionally used in lithium-air secondary batteries. Conventional electrolytes include lithium salts and organic solvents.

[0031] The metal-air battery of the present invention can be assembled into a button battery, a soft pack battery or a cylindrical battery.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The present invention constructs a new heterogeneous mixed-valence catalytic system in a high-voltage oxygen-containing lithium-oxygen battery system. The system has a highly conductive zero-valent metal and at least one oxidized metal ion as a catalytic active site. At the same time, compared with graphite, metal oxides have a more suitable adsorption energy for discharge products, and the morphology of discharge products is optimized, so that the lithium-oxygen battery using it as a positive electrode catalyst has the advantages of low decomposition voltage and high specific capacity. Using the constructed heterogeneous mixed-valence catalytic system as a positive electrode catalyst, a lithium-air battery with better comprehensive performance is obtained.

[0034] (2) The use of metal mixed valence heterogeneous catalytic systems in metal-oxygen / air batteries has not been reported. This catalytic system has extremely fast electron transport and transfer rates, which can greatly improve the performance of metal-air batteries. Due to the increased ORR / OER reaction rate, the overall performance of the battery is greatly improved.

[0035] (3) The lithium-air battery provided by the present invention selects metal M and its oxide material as a catalyst, which has simple ingredients, is environmentally friendly, low-priced and easily available, and significantly improves the cycle performance of the metal-air battery, and has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 XRD diagram of commercial Sn particles used in Example 1 of the present invention;

[0037] Figure 2 The limited capacity long cycle diagram of the lithium-air battery of Example 1;

[0038] Figure 3 The graphs are the cycle number and median voltage of the lithium-oxygen batteries of Example 1 and Comparative Example 1;

[0039] Figure 4 The limit capacity diagram of the lithium-air battery of Example 1 at different operating currents;

[0040] Figure 5 TEM image of Sn particles after the fifth cycle;

[0041] Figure 6 This is the XPS graph of Sn 3d of the pole piece in Example 1 after the first five cycles;

[0042] Figure 7 Fe@FeO prepared in Example 2 x SEM images of materials;

[0043] Figure 8 The limited capacity long cycle diagram of the lithium-air battery of Example 2;

[0044] Fig. 9 This is the SEM image of the Co@Co3O4 material prepared in Example 3;

[0045] Fig.10 The limited capacity long cycle diagram of the lithium-air battery of Example 3;

[0046] Fig.11 This is the SEM image of the CuO@Cu nanosheets prepared in Example 4;

[0047] Fig.12 The limited capacity long cycle diagram of the lithium-air battery of Example 4;

[0048] Fig.13 This is the SEM image of the Zn / Ni material prepared in Example 5;

[0049] Fig.14 This is the capacity limit long cycle diagram of the lithium-air battery of Example 5. DETAILED DESCRIPTION

[0050] In order to make the technical problem to be solved by the present invention, the technical solution, and the beneficial effects more clearly understood, the present invention is further described below in conjunction with embodiments and drawings.

[0051] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.

[0052] Embodiment 1:

[0053] Cathode catalyst preparation:

[0054] Sn metal particles are used as catalyst precursors, and the particle size is 50-2000nm.

[0055] Preparation of positive electrode:

[0056] Step 1: Disperse the catalyst material Sn metal particles and polyvinylidene fluoride (PVDF) in an appropriate amount of N-methylpyrrolidone (NMP) at a mass ratio of 9:1 (1 mL NMP for every 9 mg of catalyst), and stir for 4-6 hours to obtain a uniform paste slurry;

[0057] Step 2: Use a pipette to measure 50 μL of the slurry and evenly apply it on the surface of carbon paper with a diameter of 12 mm. Vacuum dry it at 120°C for 12 hours to obtain the positive electrode plate, which is then placed in a glove box for later use.

[0058] Lithium-air battery cell assembly:

[0059] The above-obtained positive electrode sheet and lithium metal negative electrode sheet were assembled into a lithium-air battery in a glove box filled with argon (O2 and H2O contents were both <0.1ppm), with 1M LiTFSI in DMSO as the electrolyte and a glass fiber diaphragm as the separator.

[0060] Embodiment 2:

[0061] Cathode catalyst preparation:

[0062] Fe metal particles with a particle size of 10-1000 nm were used as catalyst precursors. They were calcined in a muffle furnace at 400 °C for 1 h to obtain a mixed valence heterogeneous structure oxide thin layer Fe@FeO x , and use it as a positive electrode catalyst. According to the steps of preparing the positive electrode sheet and assembling the lithium-air battery in Example 1, a positive electrode sheet and a lithium-air battery are obtained.

[0063] Embodiment 3:

[0064] Cathode catalyst preparation:

[0065] Step 1: Synthesis of Co3O4@MgO NPs by sol-gel method

[0066] 102.8 g of Mg(NO3)2·6H2O and 167.7 g of citric acid were dissolved in 500 mL of deionized water and placed in a 500 mL beaker. Then 8.0 g of Co3O4 NPs (particle size of about 50 nm) were added to the beaker and stirred, and the resulting mixture was ultrasonically heated at 15 W for 10 min to completely disperse the Co3O4 NPs. The stoichiometric mass ratio of Co3O4 to MgO was 1:2. The resulting suspension was placed in a 500 mL beaker and placed in a water bath at 80 ° C. The five suspensions obtained were mechanically stirred until a gel was formed. The gel was dried at 200 ° C and then annealed at 800 ° C for 4 h to crystallize the MgO.

[0067] Step 2: Synthesis of Co@MgO NPs

[0068] To obtain Co@MgO, Co3O4@MgO was reduced in a H2 / N2 mixed atmosphere (500 sccm, 96% N2+4% H2) at 1000°C for 6 h.

[0069] Step 3: Synthesis of Co@Co3O4@MgO NPs

[0070] Co@MgO is annealed in air at 500-900°C (preferably 700°C) to obtain Co@Co3O4@MgO

[0071] Step 4: Preparation of Co@Co3O4 by pickling

[0072] In order to remove MgO from Co@Co3O4@MgO, 800 mg of Co@Co3O4@MgO particles were added into 20 mL of dilute HCl (the volume ratio of concentrated HCl to H2O was 8%). After reacting for 6 min, the particles were thoroughly washed with anhydrous ethanol to obtain Co@Co3O4.

[0073] The steps of preparing the positive electrode sheet and assembling the lithium-air battery in Example 1 were followed to obtain a positive electrode sheet and a lithium-air battery.

[0074] Embodiment 4:

[0075] Cathode catalyst preparation:

[0076] Step 1: Preparation of Cu nanoparticles

[0077] Usually, 0.2g Cu(NO3)2·3H2O and 1.2g PEG (Mw=4000) are dissolved in 100mL NaOH (3mol / L) and stirred vigorously at 30℃ for 1h. 2.5mL hydrazine hydrate is quickly injected into the solution and kept for 24h. The purple-black powder is collected after filtration, repeatedly rinsed with deionized water and ethanol, and vacuum dried at 60℃ for 12h to obtain Cu nanoparticles.

[0078] Step 2: Preparation of CuO@Cu nanosheets

[0079] 0.128 g of Cu nanoparticles obtained in the previous step, 30 mL of deionized water and 0.64 g of NaOH were mixed and stirred in a Teflon-lined reactor (70 mL). Subsequently, a certain amount of H2O2 was dripped into the reactor, and then the reactor was closed and heated to 110°C for 12 h. After cooling, it was rinsed several times with deionized water and ethanol, respectively, and the final product was CuO@Cu nanosheets.

[0080] The steps of preparing the positive electrode sheet and assembling the lithium-air battery in Example 1 were followed to obtain a positive electrode sheet and a lithium-air battery.

[0081] Embodiment 5:

[0082] Cathode catalyst preparation:

[0083] In the Pt mesh (20×20mm 2 ) as the anode, constant current electrodeposition of Zn crystal particles on the foam Ni sheet electrode. The electrolyte consists of an aqueous solution of 0.018M ZnCl2, 0.05M sodium citrate and 0.075M HCl. Electrodeposition was performed at 25°C for 10 minutes at different deposition currents (5, 10, 15, 20 and 25 mA) (preferably 10 mA). The prepared Zn / Ni foam was washed with ethanol and deionized water, dried at 60 degrees Celsius, and cut into 12 mm self-supporting electrode sheets for use.

[0084] The self-supporting electrode sheet was used as the positive electrode sheet, and the lithium-air battery assembly steps in Example 1 were followed to obtain a lithium-air battery.

[0085] Comparative Example 1:

[0086] According to Example 1, a lithium-air battery was assembled using carbon paper without adding a positive electrode catalyst (the carbon paper was the same as the carbon paper used in Example 1) as a positive electrode plate to obtain Comparative Example 1.

[0087] The batteries prepared in the above examples and comparative examples were tested in a sealed glass bottle filled with oxygen. Constant current charge and discharge tests were performed using a LAND test system (CT2001A). Battery test conditions: current density 200mA / g, limited capacity 1000mAh / g. Battery cycle data are shown in Table 1:

[0088] Table 1

[0089]

[0090]

[0091] The following is a further description of the technical solution of the present invention in conjunction with the accompanying drawings:

[0092] Figure 1 This is the SEM picture of the commercial Sn used. It can be seen that the Sn particles used have a particle size ranging from 100nm to 1000nm and are in the shape of small spheres.

[0093] from Figure 2 It can be seen that the Sn electrode exhibits obvious activation behavior. After the first few weeks of activation, the overpotential of the lithium-oxygen secondary battery is significantly reduced. The Sn electrode has a significantly lower overpotential and longer cycle number than the carbon paper used as the blank control ( Figure 3 ).

[0094] from Figure 4 It can be seen that the lithium-oxygen primary battery with Sn as the positive electrode catalyst has a specific capacity of 13305 mAh / g and 11268 mAh / g at current densities of 100 mA / g and 300 mA / g, respectively. Even at a high current density of 500 mA / g, it still has a high specific capacity of 8216 mAh / g.

[0095] Figure 5 This is the TEM image of Sn particles after the fifth cycle. From the image, we can see that an ultra-thin oxide layer is generated on the Sn surface.

[0096] from Figure 6 It can be seen that Sn has generated Sn on its surface after the lithium-oxygen battery cycle in the first few weeks. 0 Sn3+ Sn 4+ The above results show that the heterogeneous mixed valence catalytic system generated by metal Sn under lithium-oxygen conditions plays a good role in ORR / OER catalysis.

[0097] Figure 7 for Fe@FeO x SEM image of the material shows Fe@FeO x The particles are irregular particles.

[0098] from Figure 8 It can be seen that Fe@FeO x The electrode exhibits good catalytic ability, with a low charging platform of 3.6V and a long platform.

[0099] Fig. 9 This is the SEM image of Co@Co3O4 material. It can be seen that Co@Co3O4 is irregular elliptical particles less than 100nm.

[0100] from Fig.10 It can be seen that the Co@Co3O4 electrode exhibits good catalytic ability, with a lower charging platform of about 3.8V and a longer platform.

[0101] Fig.11 This is the SEM image of Cu@CuO material. From the image, we can see that the material morphology is nanosheet-like.

[0102] from Fig.12 It can be seen that the Cu@CuO electrode exhibits good catalytic ability and has a lower charging platform of around 3.7V.

[0103] Fig.13 This is the SEM image of the Zn / Ni material. Zn is deposited on the surface of the nickel foam in the form of rods or particles of about 1 μm, serving as a self-supporting electrode.

[0104] from Fig.14 It can be seen that the Zn / Ni electrode exhibits obvious activation phenomena similar to the Sn electrode. After the first few weeks of cycling, it shows good catalytic ability and has a lower charging platform of about 3.7V.

[0105] The specific embodiments described above further illustrate the present invention, but these descriptions cannot be understood as limiting the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A cathode catalyst material for a lithium-air battery, characterized in that: The positive electrode catalyst material is a heterogeneous structure material, which is composed of one or more zero-valent metals and at least one metal oxide, and the metal is at least one of Pd, Pt, Sn, Ti, V, Mn, Fe, Co, Ni, Cu, and Zn.

2. The cathode catalyst material for lithium-air battery according to claim 1, characterized in that: The heterostructure material is a core-shell structure, with a zero-valent metal as a core and a metal oxide layer coated on the outside as a shell.

3. The cathode catalyst material for lithium-air battery according to claim 1, characterized in that: The cathode catalyst material is in micrometer and / or nanometer size.

4. The cathode catalyst material for lithium-air battery according to claim 1, characterized in that: The cathode catalyst material is Sn@SnO x Micro-nano particles, Fe@FeO x Micro-nanoparticles, Co@Co3O4 nanoparticles, Cu@CuO nanosheets or Zn@ZnO x Micro-nano size materials.

5. A positive electrode for a lithium-air battery, characterized in that: The positive electrode for a lithium-air battery comprises the positive electrode catalyst material according to any one of claims 1 to 4.

6. The positive electrode for a lithium-air battery according to claim 5, characterized in that: The positive electrode for a lithium-air battery comprises carbon paper and a positive electrode catalyst material and a binder coated on the carbon paper.

7. The positive electrode for a lithium-air battery according to claim 6, characterized in that: The binder is polyvinylidene fluoride or polytetrafluoroethylene.

8. The positive electrode for a lithium-air battery according to claim 6 or 7, characterized in that: The positive electrode is prepared by the following method: a slurry containing the positive electrode catalyst material and the binder is dripped onto carbon paper, and the positive electrode is obtained after drying; when the metal in the positive electrode catalyst material is selected from at least one of Sn, Fe, Co, Ni, Cu, and Zn, the positive electrode catalyst material is added in the form of a heterogeneous structure material or a metal element, and the added metal element is activated into a heterogeneous structure during the charge and discharge process of the lithium-air battery, that is, a layer of metal oxide is coated on the surface of the metal element.

9. The positive electrode for a lithium-air battery according to claim 5, characterized in that: The positive electrode for the lithium-air battery is a self-supporting electrode, which includes a porous metal current collector and a metal element deposited on the current collector. The metal element is selected from at least one of Sn, Fe, Co, Ni, Cu, and Zn. The metal element is activated into a heterogeneous structure during the charge and discharge process of the lithium-air battery, that is, a layer of metal oxide is coated on the surface of the metal element.

10. A lithium-air battery, characterized in that: The lithium-air battery comprises the positive electrode according to any one of claims 5-9.